Toughness improvement of novel biobased aromatic polyamide/SEBS/organoclay ternary hybrids. Issue 29 (30th December 2019) - Lafranche, Eric; Krawczak, Patricia
ABSTRACT: Biobased aromatic polyamide/organoclay (Cloisite30B, C30B) nanocomposites were melt‐compounded with reactive and nonreactive styrene–ethylene–butylene–styrene (SEBS) rubbers at different weight contents to form ternary and quaternary blends. The mechanical properties were investigated as a function of the blend composition. The elongation at break and the impact strength increase with increasing SEBS rubber content, whereas the Young's modulus logically decreases proportionally to SEBS amount. Extra addition of SEBS grafted maleic anhydride (SEBS‐ g ‐MA) induces a synergistic effect. The SEBS‐ g ‐MA makes it possible to limit the aforementioned rigidity loss and to greatly increase the impact strength. The critical strain energy release rate increases significantly when both reactive and nonreactive rubbers are combined. Three types of microstructures appear depending on the blend composition: (1) small and numerous well‐dispersed particles when reactive rubber is used, (2) about 10 times bigger and less numerous well‐dispersed particles in the case of nonreactive rubber, and (3) a flocculated dispersion of small particles when both reactive and nonreactive rubber are added. Finally, the polyamide performances were significantly increased when the flocculated morphology was noticed due to a better PAXD/SEBS interfacial adhesion given by the SEBS‐ g ‐MA compatibilization and to a thinner rubber distribution in the matrix. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48888. Abstract : Bio‐based Polyamide investigation.